Hypolytrum pahiense, a new name for the illegitimate Hypolytrum costatum (Cyperaceae) from Liberia - Xanthos, Martin (Phytotaxa, 2013)
The genus Hypolytrum Rich. ex Pers. (Cyperaceae) is comprised of ca. 50 species (Nelmes 1955) distributed throughout the tropics and subtropics. The genus is most easily confused with Mapania Aubl., as both genera can have large basal strap-like leaves and a globose capitate inflorescence. Hypolytrum is usually distinguished by having 2 floral bracts within a spicoid compared with 4–6 floral bracts in Mapania (Simpson 1992). In Hypolytrum these floral bracts are initially fused together but then rupture to expose the maturing achene (Nelmes 1955).